Analysis Of Financial Performance In The Metal Sub-Sector And The Like On The Indonesian Stock Exchange For The Period 2018-2022 - KH, Hasbi Abdul Al-Wahhab; Hutomo, Dorojatyas Nuroska; Rodoni, Ahmad (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study was conducted with the aim of knowing the effect of Current Ratio (CR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER) and Net Profit Margin (NPM) on Return on Equity (ROE) in metal sub-sector companies and the like listed on the Indonesia Stock Exchange for the period 2018-2022. The methods used are statistical analysis and descriptive analysis, then the model selection / feasibility test, namely the chow test, followed by the classical assumption test. Meanwhile, hypothesis testing uses multiple linear regression analysis tests, t statistical tests, f statistical tests and adjusted R-squared tests. The data source of this research comes from (www.idx.co.id and www.ajaib.co.id) in the form of secondary data. The sampling technique in this study used purposive sampling technique. The data is then analyzed using panel data regression through the Eviews 10 program. Based on the results of the Classical Assumption Test, Partial Test and Simultaneous Test. It can be concluded that the results of the Classical Assumption Test show that it meets the requirements and there are no significant problems with both the Multicollinearity Test and the Heteroscedasticity Test. The results of this study indicate that CR, DAR, DER and NPM have an effect on ROE in metal sub-sector companies and the like listed on the Indonesia Stock Exchange for the period 2018-2022 either partially or simultaneously.